2015
DOI: 10.1371/journal.pone.0135585
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Correlates of Primates Conservation Status: Intrinsic Vulnerability to Anthropogenic Threats

Abstract: Behavioral traits are likely to influence species vulnerability to anthropogenic threats and in consequence, their risk of extinction. Several studies have addressed this question and have highlighted a correlation between reproductive strategies and different viability proxies, such as introduction success and local extinction risk. Yet, very few studies have investigated the effective impact of social behaviour, and evidence regarding global extinction risk remains scant. Here we examined the effects of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
3
9
0
Order By: Relevance
“…Further, the second study also found that more flexible mating systems yielded lower extinction risks (Lootvoet et al. ), which is consistent with our finding that monogamous populations consistently experienced the highest extinction risks. The reduction in extinction risk at large group sizes under alpha pair monogamy in our model could represent the relative robustness of this mating system to fluctuations in group composition.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Further, the second study also found that more flexible mating systems yielded lower extinction risks (Lootvoet et al. ), which is consistent with our finding that monogamous populations consistently experienced the highest extinction risks. The reduction in extinction risk at large group sizes under alpha pair monogamy in our model could represent the relative robustness of this mating system to fluctuations in group composition.…”
Section: Discussionsupporting
confidence: 90%
“…Under alpha pair monogamy, the results validated our initial prediction in that large group sizes reduced extinction risk in stochastic models. This result agrees with previous empirical research that has identified small group size as an important predictor of extinction risk in social mammals generally (Davidson et al 2009) and primates specifically (Lootvoet et al 2015). However, under both monogamy and polygynandry, extinction risk increased with group size, contrary to our prediction and previous empirical results (Davidson et al 2009, Lootvoet et al 2015.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…S9, A to C, and Supplementary Text). This result is likely due to the fact that related taxa share intrinsic aspects of their biology, such as body mass, life history, reproductive physiology, geographical distribution, dietary requirements, and behaviors ( 85 87 ). For example, several colobines ( Trachypithecus , Presbytis , and Simias ) in Southeast Asia are highly threatened island endemics and share biological traits known to increase their exposure and vulnerability to threats and extinction risks, such as relatively large body mass, diurnal behavior, and restricted geographic ranges.…”
Section: Factors That Threaten Primate Populationsmentioning
confidence: 99%